A closer look at weight loss interventions in primary care: a systematic review and meta-analysis - Perreault, Leigh; Kramer, E. Seth; Smith, Peter C.; Schmidt, Darren; Argyropoulos, Christos (Frontiers in Medicine, 2023)
Purpose The major aims were to quantify patient weight loss using various approaches adminstered by a primary care provider for at least 6 months and to unveil relevant contextual factors that could improve patient weight loss on a long-term basis. Methods A systematic review and meta-analysis was conducted using Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, Scopus, and Web of Science from inception to December 5, 2022. COVIDENCE systematic review software was used to identify and abstract data, as well as assess data quality and risk of bias. Results Seven studies included 2,187 people with obesity testing (1) anti-obesity medication (AOM), (2) AOM, intensive lifestyle counseling + meal replacements, and (3) physician training to better counsel patients on intensive lifestyle modification. Substantial heterogeneity in the outcomes was observed, as well as bias toward lack of published studies showing no effect. The random effect model estimated a treatment effect for the aggregate efficacy of primary care interventions −3.54 kg (95% CI: −5.61 kg to −1.47 kg). Interventions that included a medication component (alone or as part of a multipronged intervention) achieved a greater weight reduction by −2.94 kg (p < 0.0001). In all interventions, efficacy declined with time (reduction in weight loss by 0.53 kg per 6 months, 95% CI: 0.04–1.0 kg). Conclusion Weight loss interventions administered by a primary care provider can lead to modest weight loss. Weight loss is approximately doubled if anti-obesity medication is part of the treatment. Nevertheless, attenuated weight loss over time underscores the need for long-term treatment. Systematic review registration [https://www.crd.york.ac.uk/prospero/ CRD4202121242344], identifier (CRD42021242344).